2014
DOI: 10.1158/1078-0432.ccr-13-2103
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Phase I Trials for Safety in Later Trials and Final Approved Dose: Analysis of 61 Approved Cancer Drugs

Abstract: Phase I trials use a small number of patients to define a maximum tolerated dose (MTD) and the safety of new agents. We compared data from phase I and registration trials to determine whether early trials predicted later safety and final dose. We searched the U.S. Food and Drug Administration (FDA) website for drugs approved in nonpediatric cancers (January 1990-October 2012. The recommended phase II dose (R2PD) and toxicities from phase I were compared with doses and safety in later trials. In 62 of 85 (73%) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 21 publications
4
41
1
1
Order By: Relevance
“…The toxicitymortality rate described herein is similar to that in a previous report of phase I trials that evaluated anticancer drugs studied by the National Cancer Institute (mortality that was possibly drug related = 0.49%) (22,23). Other studies have also shown that safety and dose in early trials is highly predictive for later trials, possibly accounting in part for the low drug-related death rates in our registration trials (24).…”
Section: Discussionsupporting
confidence: 87%
“…The toxicitymortality rate described herein is similar to that in a previous report of phase I trials that evaluated anticancer drugs studied by the National Cancer Institute (mortality that was possibly drug related = 0.49%) (22,23). Other studies have also shown that safety and dose in early trials is highly predictive for later trials, possibly accounting in part for the low drug-related death rates in our registration trials (24).…”
Section: Discussionsupporting
confidence: 87%
“…Figure 1 shows that roughly two-thirds of oncolytic monotherapies have approved doses less than MTD. These findings are consistent with a previous review, which found that, for about 30% of compounds, MTD is not within 20% of the approved dose (23). More details are available in Supplementary Data S2 and Supplementary Fig.…”
Section: Review Of Mtd Versus Approved Dosesupporting
confidence: 92%
“…Focus is on the fact that most common side effects described in registration trials were previously accurately described in phase I trials. Moreover, they also concluded that the final approved dose was within 20% of the RP2D in the majority of trials assessed (7). However, this analysis combined MTAs and…”
Section: Discussionmentioning
confidence: 97%
“…Researchers using an exhaustive retrospective analysis have shown that a substantial proportion of clinically relevant toxicities found in registration trials were previously described in early trials. This review included data studying MTAs and conventional cytotoxics which have very different therapeutic indices and crucially did not comment on the tolerability of targeted agents in phase III clinical trials (7).…”
Section: Introductionmentioning
confidence: 99%